Driven Node Based Leach Protocol in Wireless Sensor Networks - J.Gokulraj, Dr.J.Senthilkumar, Dr.Y.Suresh, Dr.V.Mohanraj (International Journal of Advanced Science and Technology, 2020)
Wireless Sensor Networks has been the most interesting field in the collecting data from remote area where human cannot enter or monitor it has been most useful in many ways but the main problem is that sensor are powered by small battery power which makes us change the sensor more frequently to increase the performance of the network several routing protocol have been proposed, LEACH(Low Energy Adaptive Clustering Hierarchy) protocol seems to be more advantages in routing using clustering mechanism , here we propose Driver node based leach protocol which makes use of driver node in selecting the cluster head(CH) and the cluster head selects its own cluster members(CM).